Self‐Organized Kagomé‐Lattice in a Conductive Metal‐Organic Monolayer. Issue 23 (19th July 2022) - Shaiek, Nesrine; Denawi, Hassan; Koudia, Mathieu; Hayn, Roland; Schäfer, Steffen; Berbezier, Isabelle; Lamine, Chokri; Siri, Olivier; Akremi, Abdelwaheb; Abel, Mathieu
Abstract: The on‐surface synthesis of metal‐organic covalent coordination networks with a dense Kagomé lattice of metallic centers is reported. Tetrahydroxyquinone and metal atoms (M = Cu or Mn) are codeposited on Ag(111) substrate to build well‐ordered 2D lattices M3 C6 O6 . The surface is studied by scanning tunneling microscopy, low‐energy electron diffraction, and X‐ray photoelectron spectroscopy (XPS). Density functional theory (DFT) reveals a Cu + charge state and no local magnetic moments for the Cu‐organic network. For the Mn‐organic network, the charge state Mn 2+ and a local spin S = 5/2 are found. Charge transfer stabilizes the Cu + and Mn 2+ charge states. DFT calculations show a Dirac point, i.e., a band crossing with linear electron dispersion at the K‐point ( 2 / 3 ) g → a + ( 1 / 3 ) g → b $(2/3){\vec{g}_a} + (1{\rm{/}}3){\vec{g}_b}$ of the Brillouin zone. This Dirac point is at the Fermi level without charge transfer but drops by 100 meV if electron doping of Cu3 C6 O6 on Ag(111) surface is acknowledged. The magnetic couplings of an isolated Mn3 C6 O6 monolayer to be short range and antiferromagnetic leading to high frustration at the Kagomé lattice and a tendency toward a spin‐liquid ground state are predicted. In the case of hole transfer from the substrate, ferromagnetic ordering is introduced, making Mn3 C6 O6 an interesting candidate for the quantum anomalous Hall effect. Abstract : On‐surface synthesis of metal‐organic covalent coordination networks with a dense Kagomé lattice of metallic centers is presented thanks to codeposition of tetrahydroxyquinone and metal atoms (M = Cu or Mn) on Ag(111). The well‐ordered 2D lattices are studied by scanning tunneling microscopy (STM), low energy electron diffraction X‐ray photoemission spectroscopy (LEED XPS), and density functional theory calculations.